Pronomina Bahasa Melayu Riau di Desa Pulau Aro Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi - Oktoberiza, Shella Oktoberiza (J-LELC: Journal of Language Education, Linguistics, and Culture, 2022)
There are regional languages in Indonesia that have similarities and some are different. In Riau, for example, which is known by several dialects and indirectly shows the characteristics of the region. This study discusses the Riau Malay Pronouns in Pulau Aro Village, Kuantan Tengah District, Kuantan Singingi Regency. The problem in this research is to analyze personal pronouns, suggestive pronouns, and questioner pronouns. The purpose of this research is to explain personal pronouns, pointing pronouns, and pen pronouns in Pulau Aro Village. The theory that is used as a guide in this research is Alwi et al., (2003) dan Chaer, (2008),. The method used by the author in this study is a descriptive method and the approach that the author uses in this study is a qualitative approach. Data collection technique in this research is interview. The results of this study can be concluded that the personal pronouns found in Pulau Aro Village, Kuantan Tengah District, Kuantan Singingi Regency have 30 pronouns, 21 indicating pronouns, and 19 pronouns asking the questioner.